(3GdeHOC hGdeYGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hHYO , aCfi CQjO Cf COd Ydi MbjbI eG YfO ebGdJi gPg s
(3BNQgG (B:s
(3hdcf eDKQ GdEjVGM hGdGNJUGQ hJbQjH GdHYjO s
(3GfXQ QSGdI ai GdeHOC Ch GdeYGO (B" (3Qbe (B" 173" (3adSaI hefWbs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GeHQhRjGfG (B(2/150) s
Keywords: (3GdadSaI hGdefWbs